The effect and mechanism of miR-30e-5p targeting SNAI1 to regulate epithelial-mesenchymal transition on pancreatic cancer. Issue 4 (1st April 2022) - Liang, Ziyu; Tang, Shaomei; He, Rongquan; Luo, Wei; Qin, Shanyu; Jiang, Haixing
ABSTRACT: Accumulating evidence indicates that abnormally expressed microRNAs (miRNAs, miRs) contribute to cancer progression. Nonetheless, the role of miR-30e-5p in pancreatic cancer (PCa) remains unclear. In this study, using quantitative real-time polymerase chain reaction analysis, we found that miR-30e-5p expression was downregulated in human PCa tissues compared with that in normal para-cancerous tissues. After transfecting with miR-30e-5p inhibitors, miR-30e-5p mimics, or empty vectors in the BxPC-3 and PANC-1 cells, respectively, the experiments revealed that the upregulation of miR-30e-5p expression inhibited cell growth, invasion, migration and epithelial-mesenchymal transition (EMT), and promoted apoptosis, while miR-30e-5p downregulation had the opposite effects. RNA sequencing of miR-30e-5p inhibitor-, miR-30e-5p mimic-, and the negative control (NC)-treated groups revealed that miR-30e-5p may affect epithelial cell differentiation, cell growth and death. Next, the snail family transcriptional repressor 1 (SNAI1) was predicted and verified as the target gene of miR-30e-5p using bioinformatics analysis and luciferase assays. SNAI1 expression levels were decreased in the PCa cells transfected with miR-30e-5p mimics, whereas the opposite was observed in the cells transfected with miR-30e-5p inhibitors. Subsequently, PCa cells were transfected with a vector overexpressing SNAI1 (OE-SNAI1) and miR-30e-5p mimics, miR-30e-5p inhibitors, or empty vectors. Compared with that in the OE-SNAI1 + miR-30e-5p NC group, transfection with OE-SNAI1 + miR-30e-5p mimics inhibited the PCa cell growth, migration, and increased apoptosis, whereas transfection with OE-SNAI1 + miR-30e-5p inhibitors had the opposite effects. In conclusion, miR-30e-5p potentially inhibits PCa cell proliferation, migration, and invasion via the SNAI1/EMT axis.